Perceptions of Covid-19 vaccine among life science students of a Tertiary Institution in Nigeria - Phillip , Iquo Oyohosuho; Phillip, Julius Oyohosuho; Ita, Abigail Asukwo (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
The COVID-19 pandemic has had a profound impact on global populations, resulting in over 5 million deaths worldwide as of September 2021. The development and widespread distribution of vaccines have emerged as crucial strategies for combating the spread of COVID-19. This research endeavours to investigate the acceptance of COVID-19 vaccines among life science students at the University of Calabar, Nigeria. The study presents an analysis of the socio-demographic characteristics of 500 respondents, revealing that 182 individuals (36.4%) expressed acceptance of the vaccine, while 318 individuals (63.6%) declined it. Personal reasons emerged as the most prevalent factor influencing vaccine acceptance, followed closely by concerns regarding potential side effects. Additionally, the research findings indicate that a minority of respondents perceive the COVID-19 vaccine as effective, yet a significant proportion harbour beliefs in various myths surrounding the vaccine, notably the misconception that it contains microchips. Furthermore, the study underscores the importance of targeted interventions aimed at addressing individual concerns and enhancing awareness regarding the safety and efficacy of the COVID-19 vaccine while dispelling prevalent myths. These efforts are crucial in fostering increased vaccine uptake and promoting public health resilience against the ongoing pandemic. Finally, the results emphasise the ongoing necessity for comprehensive educational initiatives aimed at informing and enlightening the public about the significance of COVID-19 vaccination in curtailing the transmission of the disease.